Perilaku Mencatat dan Kemampuan Memori pada Proses Belajar - Dewi, Ida Ayu Gede Bintang Praba; Indrawati, Komang Rahayu (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2014)
Learning is a process or activity that would not stop in a person lifetime. Learning can be done by anyone and anywhere. One of the learning process occur in the school environment. Each student has an individual learning style that suits their convenience. The result of the study will further improve if aided by the accompanying media that is taking notes. Taking notes is included in the learning process when done with awareness and without enforcement from others. Taking note behavior will help students understanding the perception of memory skill in learning process. Due to the reasons above, the researcher wants to look relationship between the attitude of taking note behavior towards the attitude of memory skill in learning process. The research methodology is quantitative, used 166 subjects whom are grade 2 science, high school students in Denpasar, with 15 to 17 years old age range. The correlation coefficient is 0,442 with 0,000 probabilities. This mentioned results shows that there is a relationship between the attitude of taking note behavior towards the attitude of memory skill in learning process. The determination coefficient is 0,195. The analysis method in this research is simple regression. Statistical analysis showed that the attitudes of taking note behavior can be used to predict attitudes of memory skill. When individuals have attitude of taking note behavior, then the individual will able to see as far as which the attitude of memory skill within each individual. Keyword: Attitude of taking note behavior, Attitude of Memory Skill, Student